Applied Psychology Readings Selected Papers from Singapore Conference on Applied Psychology, 2016 - Leung, Man-Tak.; Tan, Lee Ming.; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
This book features the best papers presented at the Singapore Conference on Applied Psychology in 2016. Chapters include research conducted by experts in the field of applied psychology from the Asia-Pacific region, and cover areas such as community and environmental psychology, psychotherapy and counseling, health, child and school psychology, and gender studies. Put together by East Asia Research (Singapore), in collaboration with Hong Kong Shue Yan University, this book serves as a valuable resource for readers wanting to access to the latest research in the field of applied psychology with a focus on Asia-Pacific.
Preface -- Editors -- SCAP Committee -- The phenomenology and ontology of the Oedipus Complex -- The behavioral related conditioned sound in cross modal Stroop task -- Mediamultitaskers and attentional bias towards emotional stimuli -- Cognitive deficits and depression among diabetic and non-diabetic patients with coronary heart disease -- Sex differences and emotion in wayfinding: Use a map or verbal direction (a pilot study) -- Moral emotions: An explorative study on elementary school teachers of Yogyakarta -- A structural equation model of WhatsApp's addiction, emotion regulation, personality, academic performance decrement and social connection of WhatsApp's attitude -- The relationship between personality traits, school climate, parental relationship, anxiety, depression, self-esteem and cyber-victimization -- Differences in participant motivation based on category of body mass index and gender -- Participant motivation predicting training sessions and training type in male and female athletes competing at 2010 Pan Pacific Masters Games -- The structural relationships between foreign language speaking anxiety, perceived English competence, English learning motivation, willingness to communicate, English learning engagement and motivational intensity in Hong Kong secondary students -- The structural model of perceived parenting style as antecedent on achievement emotion, self-regulated learning and academic procrastination of undergraduates in Hong Kong -- Pathways to bullying and victimisation- psychological perspectives -- Adult attachment internal working model of self and other, self-esteem and romantic relationship satisfaction in Chinese culture: By multilevel-multigroup structural equation modelling -- The psychometric properties of the Individual-Oriented Achievement Motivation Scale - Short Form (IOAMS - SF): By structural equation modelling (SEM) and item response theory (IRT). .
Keywords: Applied psychology; Psychology, Clinical; Developmental psychology; Consciousness